The Influence of Financial Literacy and The Use of E-Wallets on The Consumptive Behavior of Generation Z in Medan City - Julita Julita (Journal of Management and Business Innovations, 2026)
The rapid development of financial technology has transformed payment systems, particularly through the widespread use of e-wallets among Generation Z. While digital payment services provide convenience and efficiency, they may also encourage excessive consumptive behavior if not accompanied by adequate financial literacy. This study aims to analyze the influence of financial literacy and e-wallet usage on the consumptive behavior of Generation Z in Medan City. This research employed a quantitative associative approach using questionnaire data collected from 100 Generation Z respondents who actively use e-wallets. Data were analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM). The structural model assessment shows that e-wallet usage significantly increases consumptive behavior (, , ) while better financial literacy helps individuals make more rational financial decisions and controls impulsive spending. These findings contribute to the growing literature on digital financial behavior and provide practical implications for improving financial literacy among Generation Z.Keywords: Consumptive Behavior,  Digital payment, E-Wallet, Financial Literacy